2017
DOI: 10.1002/cncr.31154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disease‐free survival as an intermediate metric of overall survival in patients with localized renal cell carcinoma: A trial‐level meta‐analysis

Abstract: Across RCTs of adjuvant systemic therapy for localized RCC, there was no strong correlation noted between 5-year DFS and 5-year OS rates or between treatment effects on these endpoints. These results highlight the need to identify alternative and more rapid clinical or biologic endpoints to hasten drug development and improve clinical outcomes. Cancer 2018;124:925-33. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…This data suggests a suppressive role of angiogenesis on T cell-inflammation and may support further development of VEGFR2-TKI in combination or sequential therapy with ICI in earlier stage ccRCC. In clinical trials in non-metastatic ccRCC, perioperative systemic treatment with VEGFR2-TKI was not shown to increase overall survival versus surgery alone [5759]. Benefit from ICI in the adjuvant and neoadjuvant setting has been observed in multiple cancers including NSCLC, breast cancer and melanoma and multiple phase III clinical trials evaluating ICI in ccRCC in both adjuvant and neoadjuvant settings are ongoing [6064] (NCT03024996, NCT03142334, NCT03055013).…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests a suppressive role of angiogenesis on T cell-inflammation and may support further development of VEGFR2-TKI in combination or sequential therapy with ICI in earlier stage ccRCC. In clinical trials in non-metastatic ccRCC, perioperative systemic treatment with VEGFR2-TKI was not shown to increase overall survival versus surgery alone [5759]. Benefit from ICI in the adjuvant and neoadjuvant setting has been observed in multiple cancers including NSCLC, breast cancer and melanoma and multiple phase III clinical trials evaluating ICI in ccRCC in both adjuvant and neoadjuvant settings are ongoing [6064] (NCT03024996, NCT03142334, NCT03055013).…”
Section: Discussionmentioning
confidence: 99%
“…However, some ongoing clinical trials may provide evidence for the future adoption of adjuvant therapy such as new tyrosine kinase inhibitors and nivolumab. One study suggested that full-dose sunitinib could improve DFS in a subset analysis (51, 52). Therefore, we could expect the clinical results of several trials involving adjuvant new TKIs or combined with immune checkpoint inhibitors in the following years.…”
Section: Discussionmentioning
confidence: 99%
“…To address this clinical need, multiple trials have investigated the addition of systemic therapy after surgery in nonmetastatic disease based on effectiveness in the metastatic setting [4]. However, despite over 13 randomized trials testing adjuvant systemic therapies in the last 40 years [5], there has been only one positive study. In this trial highlight, we discuss the recent controversy over the adjuvant use of targeted therapies and highlight the ongoing trials of perioperative immune checkpoint blockade with a focus on the PROSPER RCC Study.…”
mentioning
confidence: 99%